Ice Force and Scour Instrumentation for the White River, Vermont. - Zabilansky, Leonard J. (1996)
In January 1990 a bridge over the White River in White River Junction, Vermont, collapsed during a period of ice breakup. Based on the historic weather and stage data, the bridge had survived more dramatic breakups in previous winters. The ultimate failure was attributed to the progressive deterioration of the foundation due to scour. Twenty years of weather and stage data at the site are presented along with a failure scenario. Instrumentation to measure the ice forces on a bridge pier was incorporated into the design of the replacement bridge. Recognizing scour as the primary cause of failure, the new bridge piers have extensive scour protection. A pier for a bridge 2000 feet upstream of the new bridge was instrumented for scour. The objective was to develop real-time scour monitors that would survive ice and debris and allow correlation between the hydrograph and scour activity. Instrumentation and data acquisition packages for both instrumented bridge piers are presented. The results of the first two years of measurements are presented. Both winters were relatively mild, consequently the breakup loads were low. The maximum dynamic load was 26 kips, which, with a 4-foot-wide panel and 12 inches of ice translates to an ice pressure of 45 psi. The scour measurements were of extreme interest. The bulk of the scour occurred in the initial stages of breakup while the ice sheet was still intact. Apparently to compensate for the fixed ice surface, the mean velocity had to increase as the discharge increased. The faster velocity resulted in more aggressive bed scour. Once the ice sheet broke up and the ice was free floating, the scour activity subsided.